Método de Análisis Temporal para Root Cause Analysis en Redes Móviles - Luo Chen, Hao Qiang; Khatib, Emil Jatib; Suárez Peña, José Ramón; Barco-Moreno, Raquel (My University, 2019)
Troubleshooting encompasses a variety of processes required for the solution of mobile network degradations. These netwoks usually operate correctly, thanks to automatized processes of configuration and optimization, but such degradations may happen due to diverse unpredicted reasons and their impact is negative from the user perspective, since the service quality degrades. For that, Root Cause Analysis (RCA) is the step which accomplishes the task of searching the origin of those degradations. In this paper, an automatic RCA method based on temporal analysis of the general behavior of network elements and its correlation with individual counters is presented.
Keywords: Sistemas de comunicaciones móviles; Root Cause Analysis; Smart Networks; Dependable Networks; Self-Organizing Map; Correlation